A guide to writing a sound research proposal - Zondi, Wellington B. (Opción, 2019)
This paper aims to provide a theoretical framework for the students who are about to write their research proposal, with the aim of a non-scientific method of acquiring knowledge based on the description given by Bless et al. (2013). This paper first provides a definition of the research process and goes further to provide a distinction between a scientific and non-scientific research approach. That is followed by an overview of what scientific research ought to be. A suggested template of the research proposal is then given, providing a brief description of each heading and sub-headings